ELEKTRODA PASTA KARBON YANG DIMODIFIKASI OLEH AMPAS TEBU TERAKTIVASI UNTUK ANALISIS ION CR(VI) SECARA VOLTAMMETRI - Annisa Anggitami; Ria Sri Rahayu; Muhammad Yudhistira Azis (CHEDS: Journal of Chemistry, Education, and Science, 2023)
Heavy metal pollution, particularly chromium (Cr) contamination, poses a significant threat to the environment due to improper waste processing in industries such as electroplating. This study focuses on the development of a sensitive analysis method using voltammetry to detect low concentrations of toxic Cr(VI) ions in environmental samples. The use of activated bagasse as an efficient, cost-effective, and environmentally friendly sensor is explored. The surface area of the carbon paste electrode is increased by modifying it with activated bagasse, which enhances the measurement sensitivity. Optimization of the measurement techniques and sample analysis is carried out, including the activation of bagasse and the composition of the activated graphite:bagasse (BG) electrode. The optimal condition for measurement is achieved with a 5% (w/w) composition of activated graphite:BG electrode. The modified electrode exhibits good repeatability, with a linear range of 1-1000 μM and a detection limit of 0.5373 μM. The %RSD values obtained using Differential Pulse Voltammetry (DPV) and Square Wave Voltammetry (SWV) are 4.794% and 3.593%, respectively. Analysis of the scan rate suggests that the electron transfer process is controlled by adsorption. The activated electrode is successfully applied to analyze artificial samples, and the results are comparable to those obtained using the Atomic Absorption Spectroscopy (AAS) method.